Bibliometric Analysis of Social Media Marketing and Hospital Brand Credibility: A Systematic Mapping Review - Guntur Adi Wibowo; Aflit Nuryulia Praswati; Yusuf Alam Romadhon (Indonesian Health Issue, 2026)
Background: The development of social media has driven a transformation in hospital healthcare marketing strategies, making the formation of brand credibility through digital platforms an important issue. Objective: This study aims to systematically map and analyze the development of research on social media marketing and its relationship with the formation of hospital brand credibility, with a focus on the roles of brand awareness, brand trust, and parasocial relationships. Methods: This study employed a systematic mapping review approach guided by PRISMA stages in the processes of literature identification and selection. Data were obtained from the Scopus database on June 26, 2025. A total of 26 scientific articles were selected through identification, title and abstract screening, and eligibility assessment based on inclusion criteria. The reviewed studies were predominantly quantitative, employing survey-based methods and structural equation modeling, with a smaller proportion using mixed-method approaches. Data analysis was conducted using a bibliometric approach with VOSviewer software to map publication trends and conceptual relationships among variables. Results: The analysis indicates an increase in the number of publications since 2021, with dominant themes related to digital branding, consumer trust, and emotional interaction through social media. Keyword mapping shows that brand awareness and brand trust are key conceptual nodes closely connected to parasocial interaction and brand credibility. The reviewed studies indicate positive relationships between social media marketing activities, increased brand awareness and brand trust, and the formation of brand credibility, although the strength of these relationships varies across studies. Conclusion: Social media marketing plays a role in strengthening hospital brand credibility through enhanced brand awareness, trust formation, and the reinforcement of psychological relationships with audiences. These findings represent a synthesis based on literature mapping and do not yet reflect direct causal measurement; therefore, further empirical research is still required.